2013
DOI: 10.1159/000352051
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Applications of the Montreal Cognitive Assessment for the Assessment of Vascular Cognitive Impairment

Abstract: Cognitive impairment is common among patients with stroke or other cerebrovascular disease and influences long-term outcome, including occupational functioning. Recognition and monitoring of mild cognitive impairment is thus essential to good patient care. The Montreal Cognitive Assessment (MoCA) has been suggested as a brief screening test of vascular cognitive impairment. This paper presents a critical review of the research literature evaluating the validity and utility of this test with the aim of informin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 50 publications
(91 reference statements)
2
58
0
2
Order By: Relevance
“…The cutoff point of <25, <24, <23 in MoCA scores [20] must be taken under the reserve that cutoff points must be established appropriate to culturally context and maybe that the bonus point given to those having under 12 years of schooling is just not enough to homogenize the subjects capacity of completing the questionnaire [21].…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff point of <25, <24, <23 in MoCA scores [20] must be taken under the reserve that cutoff points must be established appropriate to culturally context and maybe that the bonus point given to those having under 12 years of schooling is just not enough to homogenize the subjects capacity of completing the questionnaire [21].…”
Section: Discussionmentioning
confidence: 99%
“…Чувствительность и специфичность MMSE и МоСА в разных возрастных группах вариабельны и зависят от нейропсихологического профиля и уровня образования [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Кроме того, большин-ство шкал адаптировано к амбулаторной оценке и их использование в условиях стационара может быть затруднено.…”
Section: Discussionunclassified
“…Порог отсечения, который обсуждается для шкалы МоСА, вариабелен, однако большинство авторов указывают на значение 24-26 баллов [14][15][16][17][18][19]. В нашей работе максимальную чувствитель-ность и специфичность (65,0 и 77,8% соответствен-но) удалось получить при крайне низком пороге отсечения в 19 баллов.…”
Section: Discussionunclassified
“…MoCA usually cover frontal lobe function than MMSE. 23 Patients with VCI usually manifest more frontal lobe dysfunction than temporo-parietal lobe dysfunction, and therefore, subtle clinical changes undetected in MMSE are reflected in MoCA-K. These findings suggested that an appropriate choice of primary outcome measures is important in clinical trials.…”
Section: Dementia and Neurocognitive Disordermentioning
confidence: 99%